Facts about Vitamins - R. Elaine Turner (EDIS)
FCS8808, a 4-page fact sheet by R. Elaine Turner, discusses what vitamins are, what they do, and why we need them. It also provides information on how to cook foods to preserve vitamins and how to assess food labels, and gives tips on appropriate and inappropriate use of vitamin supplements. Published by the UF Department of Family, Youth and Community Sciences, December 2006.